Connection of large amplitude angular jump motions with temporal heterogeneity in aqueous solutions. Issue 17 (20th April 2020) - Das Mahanta, Debasish; Mitra, Rajib Kumar
Abstract : A new methodology to describe temporal heterogeneity in aqueous solutions through large amplitude angular jump motions. Abstract : It has now been established that large angular jumps do take place when a rotating water molecule exchanges its hydrogen bond (H-bond) identity. This motion differs from the small angular diffusional steps occurring within short time intervals which define the ' Debye diffusion model ' of water dynamics. We intend to investigate whether these two processes do eventually complement each other. In this present investigation the orientational dynamics of water in its mixture with a small hydrophobic molecule 1, 2-dimethoxy ethane (DME) is studied microscopically using the all-atom classical molecular dynamics (MD) simulation technique. We found that the reorientational motions of water molecules are governed by continuous making and breaking of intermolecular H-bonds with their partners. We characterise these H-bond reorientation motions with the description of the " large amplitude angular jump model " and explore the coupling between the rotational and translational motions. By following the trajectories of each molecule in the solutions we describe the orientational dynamics of liquid water with a ' continuous time random walk ' (CTRW) approach. Finally, we explore the diffusivity distribution through the jump properties of the water molecules, which successfully leads to the inherent transient heterogeneity of the solutions. We observe that the heterogeneity increases with increasing DME content in the mixtures. Our study correlates the coupling between rotational and translational motions of water molecules in the mixtures.